Potential Adiponectin Receptor Response Modifier Therapeutics - Otvos, Laszlo (Frontiers in Endocrinology, 2019)
Many human diseases may benefit from adiponectin replacement therapy, but due to pharmacological disadvantages of the intact protein, druggable options focus on peptidic and small molecule agonists of the adiponectin receptor. Peptide-based adiponectin replacement drug leads are derived from, or resemble, the active site of globular adiponectin. ADP355, the first-in-class such peptide, exhibits low nanomolar cellular activities and clinically acceptable efficacies in a series of fibrotic and inflammation-derived diseases. The advantage of small molecule therapies, spearheaded by AdipoRon, is oral availability and extension of utility to a series of metabolic conditions. It is exactly the difficulties in the reliability and readout of the in vitro measures and the wealth of in vivo models that make comparison of the various drug classes complicated, if not impossible. While only a fewer number of maladies could take advantage of adiponectin receptor antagonists, the limited number of these available can be very useful tools in target validation studies. Alternative approaches to direct adiponectin signaling control use upstream adiponectin production inducing therapies but currently these offer relatively limited success compared to direct receptor agonists.